2013
DOI: 10.1002/hep.26532
|View full text |Cite
|
Sign up to set email alerts
|

Jet-fixation: A novel method to improve microscopy of human liver needle biopsies

Abstract: example, hepatocellular carcinoma). In this regard, we did not exclude patients with high MELD (range in our study 5 to 28) nor did we omit patients with renal insufficiency. This allowed a clear and unbiased evaluation of feasibility, efficacy, and safety of the intervention in a broad range of a homogenous group of patients. Based on this uncensored approach, we were able to perform uni-and multivariate analysis in a large enough population and make an estimate of the ideal cutoff point of the MELD score, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…In recent years, the author (E. W.) had the opportunity to investigate more than 200 wedge and needle biopsies of human livers using fixation methods adapted to obtain perfusion fixation quality tissue. 52 , 53 After observing these specimens, the author concluded that no cells with rat pit cell morphology are present in the human liver. Very occasionally, a cell with a few granules could be found, but an EM comparison of rat and human livers led to the conclusion that human liver does not harbor a morphological equivalent of the rat pit cell.…”
Section: Liver Nk Cell Subsetsmentioning
confidence: 99%
“…In recent years, the author (E. W.) had the opportunity to investigate more than 200 wedge and needle biopsies of human livers using fixation methods adapted to obtain perfusion fixation quality tissue. 52 , 53 After observing these specimens, the author concluded that no cells with rat pit cell morphology are present in the human liver. Very occasionally, a cell with a few granules could be found, but an EM comparison of rat and human livers led to the conclusion that human liver does not harbor a morphological equivalent of the rat pit cell.…”
Section: Liver Nk Cell Subsetsmentioning
confidence: 99%
“…Samples were fixed using a modified set-up of the “jet-fixation” method described by {Vreuls et al 53. #2@@author-year}.…”
Section: Methodsmentioning
confidence: 99%
“…All procedures were conducted in accordance with the guidelines and approval of the Animal Care and Ethics Committee of the University of Sydney. A strip of liver tissue measuring ∼1 × 1 × 15 mm 3 was fixed by means of “jet‐fixation” as described by Vreuls et al () in a solution containing 1.5% glutaraldehyde in 0.067 M sodium cacodylate buffer, 1% sucrose and 2 mM calcium chloride pH 7.4 at 37°C. Following jet‐fixation, the tissue was cut into ∼1 mm 3 blocks and allowed to react in the primary fixative for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%